2018
DOI: 10.1016/j.joen.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Large Periapical or Cystic Lesions in Association with Roots Having Open Apices Managed Nonsurgically Using 1-step Apexification Based on Platelet-rich Fibrin Matrix and Biodentine Apical Barrier: A Case Series

Abstract: Teeth having open apices in the absence of a natural apical constriction pose several challenges during conventional endodontic treatment, especially when establishing an apical seal. Treatment is further challenging when these teeth are associated with large periapical or cystic lesions having resulted in expansion and/or thinning of adjacent cortical plates. Although surgical intervention is commonly adopted in the management of such cases, a conservative treatment option offering equally good prognosis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
0
24
0
4
Order By: Relevance
“…However, compared with calcium hydroxide the cost of these two treatment modalities are higher. The main advantage of these treatment modalities is A research [17] was carried out by Kunhappan (2016) to study about the use of MTA and triple antibiotic up radiographs shows the apical seal of MTA and the It has been proved that, even large periapical lesions can respond favorably to nonsurgical treatment with rich Fibrin in healing large periapical lesions The study has concluded a collective approach strategy involving 1-step apexification using PRF and Biodentine and supplemented with lesion decompression under a stringent disinfection protocol proved highly successful in enabling teeth with open apices and large periapical/cystic lesions to return to a state of health and function without surgical intervention [18].…”
Section: Fig 1 Randomly Selected Cases To Calcium Hydroxidementioning
confidence: 95%
See 2 more Smart Citations
“…However, compared with calcium hydroxide the cost of these two treatment modalities are higher. The main advantage of these treatment modalities is A research [17] was carried out by Kunhappan (2016) to study about the use of MTA and triple antibiotic up radiographs shows the apical seal of MTA and the It has been proved that, even large periapical lesions can respond favorably to nonsurgical treatment with rich Fibrin in healing large periapical lesions The study has concluded a collective approach strategy involving 1-step apexification using PRF and Biodentine and supplemented with lesion decompression under a stringent disinfection protocol proved highly successful in enabling teeth with open apices and large periapical/cystic lesions to return to a state of health and function without surgical intervention [18].…”
Section: Fig 1 Randomly Selected Cases To Calcium Hydroxidementioning
confidence: 95%
“…Sarang et al [18] has used Biodentine and Platelet nonsurgically in their study. The follow MTA and Biodentine are more novel materials which are recommended to be used for successful apical closure in cases with large periapical lesions.…”
Section: Fig 1 Randomly Selected Cases To Calcium Hydroxidementioning
confidence: 99%
See 1 more Smart Citation
“…É necessária a ação de um agente inflamatório, por exemplo, capaz de estimular e determinar a proliferação desses remanescentes 10 . Tal condição é Revista de Iniciação Científica em Odontologia 2018;16(3):151-158. frequente nos maxilares, onde infecções e traumas são capazes de desencadear a resposta inflamatória 3,4,10,11 .…”
Section: Introductionunclassified
“…Os COs tendem a aumentar lentamente de tamanho, possivelmente em resposta ao aumento da pressão osmótica luminal. Genericamente estas lesões podem: ser assintomáticas, variar de milímetros a alguns centímetros e costumam causar deslocamento de estruturas adjacentes (como dentes, raízes e nervos) 4 . Radiograficamente costuma ser visível uma imagem radiolúcida, unilocular, de limites bem definidos e rodeada por uma margem de osso esclerótico 4,5,6 .…”
Section: Introductionunclassified